What Does it Mean to be a Woman? How the Content of Gender Identity May Facilitate Women’s Coping with Sexual Harassment - Western, Kate A. B. (Journal of interpersonal violence, 2022)
Sexual harassment and other forms of gendered discrimination are social psychological phenomena, yet the psychological impact of sexual harassment has rarely been examined through a model which considers the role of diverse content of gender identity (i.e. norms). We used an experimental design to investigate how salient norms associated with the social identity of ?women? affect coping with sexual harassment. Participants who identified as women (N = 291) were randomly assigned to either a feminist, traditional feminine, or control norm condition, in which the salience of particular norms associated with womanhood was manipulated. Participants completed measures of personal growth (as a proxy for post-traumatic growth), and help-seeking intentions in response to a hypothetical sexual harassment scenario. Participants in the feminist condition reported significantly greater personal growth relative to those in the traditional feminine and control conditions. Participants in both the feminist and traditional feminine conditions reported significantly greater intentions to seek help from formal supports (e.g. primary care doctor), relative to those in the control condition. The findings suggest that the salience of social identities and their content may be valuable resources in promoting recovery following experiences of gendered discrimination and support the role of social identities in influencing post-trauma trajectories.